Improving Student Learning Activities through the Problem Based Learning Model in Islamic Learning at SD Negeri Rantau Gedang - Mawarni, Samsi; Jambeh, Abdul (Journal of Indonesian Primary School, 2025)
This classroom action research is entitled "Improving Learning Activities on the Material of the Prophet's Hijrah to Medina Through the Problem Based Learning Model for Grade IV Students of Rantau Gedang Elementary School in the 2024/2025 Academic Year" based on the title the author wants to use the problem based learning model in learning Islamic Religious Education at Rantau Gedang Elementary School grade IV, because with this PBL model it is hoped that students will be more active and enthusiastic in the learning process of Islamic Religious Education on the material of the Prophet's hijrah to Medina, in learning before using this problem based learning students were still less active and learning outcomes did not improve. The type of research used in this study is classroom action research, namely using cycles, cycle I and cycle II, the aim is to be able to find the stages of success or completeness of student learning. From the results of the study the author found the success of the learning objective completion criteria. At the stage of cycle I it was still below the standard, the percentage of student learning outcomes was only 53%, 8 out of 15 students achieved the minimum completeness criteria, then in cycle II it had reached above the standard, the percentage of student learning outcomes reached 93%. Thus, the minimum expected completion criteria have been achieved in the learning of Islamic Religious Education on the material of the Prophet's Hijrah to Medina in class IV of Rantau Gedang State Elementary School, Singkil District, Aceh Singkil Regency.